2005
DOI: 10.1111/j.1447-0756.2005.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a prediction method for premature rupture of membranes in term pregnancy using active ceruloplasmin in cervicovaginal secretion as a clinical marker

Abstract: Active ceruloplasmin in the cervicovaginal secretion might be a reliable clinical marker for term PROM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Peroxidation of membrane lipids decreases membrane fluidity and impairs membrane barrier function. We demonstrated that an oxidative stress occurring in a phase of developmental growth may injure many foetal organs and tissues, impairing the normal growth potential [25]. To what extent oxidative stress can induce metabolic and developmental foetal growth deregulation is unknown.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Peroxidation of membrane lipids decreases membrane fluidity and impairs membrane barrier function. We demonstrated that an oxidative stress occurring in a phase of developmental growth may injure many foetal organs and tissues, impairing the normal growth potential [25]. To what extent oxidative stress can induce metabolic and developmental foetal growth deregulation is unknown.…”
Section: Resultsmentioning
confidence: 98%
“…Discussion P-PROM is diagnosed when clinically apparent leakage of amniotic fluid is confirmed in pregnant women without uterine contractions or vaginal bleeding before the 37 weeks' gestation [25]. P-PROM is characterized by reduced collagen concentrations, altered collagen cross-link profiles and increased concentrations of biomarkers of oxidative damage [3].…”
Section: Resultsmentioning
confidence: 99%
“…14,15 Recent studies have detected a correlation between several immuneresponse molecules in CVF and the incidence of subclinical premature rupture of membranes (PROM), which leads to preterm birth. 16,17 During pregnancy, CVF could contain amniotic fluid (AF) derived from the uterus, due to either the disruption or parallel secretions of the chorionic-decidual interface. This "leakage" of AF into CVF provides the basis for the current noninvasive diagnosis for the presence of the fetal fibronectin, which has been used to predict preterm labor in women.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased levels of inflammatory cytokines are also associated with preterm delivery (Kalinka, 2005). Neutrophil elastase, secretory leukocyte protease inhibitor, and active ceruloplasmin are correlated with subclinical premature rupture of membranes (PROM) and lead to preterm birth (Helmig et al, 2002;Ogino et al, 2005). Thus, CVF may be an important potential diagnostic site to monitor maternal and fetal health during pregnancy because of its minimally invasive collection method as compared to AF.…”
Section: A Proteomic Analysis Of Cvf During Pregnancymentioning
confidence: 97%